Pengaruh perceived organizational support terhadap work engagement: peran mediasi affective commitment dan moderasi co-worker support - Diah Nafisa Putri (Jurnal Ilmu Manajemen, 2023)
This study aims to examine and analyze the effect of perceived organizational support on work engagement with the mediating role of affective commitment and the moderating role of co-worker support among employees of PT. Pelabuhan Indonesia (Persero) Regional 3 Surabaya Office. This research is quantitative. The sampling technique used proportionate stratified random sampling with 54 employees as a sample. The statistical analysis used in this research is Partial Least Squares (PLS) with the help of WarpPls 7.0 software. The results of this study explain that perceived organizational support has a positive and significant effect on work engagement. Perceived organizational support has a positive and significant effect on affective commitment. Affective commitment has a positive and significant effect on work engagement. Affective commitment partially mediates the effect of perceived organizational support on work engagement. Co-worker support does not moderate the effect of affective commitment on work engagement.